Pharmacognostical, Phytochemical, Antioxidant and Antimicrobial Activity of Costus woodsonii - Sikarwar, Mukesh S; Szeek, Chew Khai; Paliwal, Neeraj (Edelweiss Applied Science and Technology, 2019)
Background: Herbal medicine mostly contains wide range of chemical compounds responsible for medicinal therapeutic use. Costus woodsonii is commonly called as Red Button Ginger and synonyms of the botanical name are Costus spiralis, Alpinia spiralis and Costus pisonis. In Malay, it is known as Setawar Halia Merah. In Chinese, it is known as Hong Bi Qiao Jiang. Objective: This research was conducted to study the pharmacognostical, phytochemical, antioxidant and antimicrobial activity of C. woodsonii leaf extracts. Method: Macroscopy, microscopy, phytochemical analysis, thin layer chromatography, antioxidant activity and antimicrobial activity of C. woodsonii leaf were carried out. Total flavonoids were estimated in the leaf extract. The total phenolic content of C. woodsonii leaf was determined using Folin-Ciocalteu reagent. The antioxidant activity of leaf extract of C. woodsonii was determined by performing DPPH radical scavenging. The microbial activity was determined by Well diffusion test, MIC (Minimum Inhibitory Concentration) test and MBC (Minimum Bactericidal Concentration) test. Result and Discussion: C. woodsonii belongs to costaceae with elliptical green leaves. Till now are no extensive studies on C. woodsonii. Preliminary phytochemical analysis revealed the presence of flavonoid, steroid, fat, phenol, tannin and mucilage in leaf extract. Physicochemical studies further revealed the ash value of leaf as 8.7%. Among the three extractions, alcohol extractive values showed the highest as 13%. Loss on drying at 105 degree Celsius in leaf was found to be 12.67%. The plant extract showed total phenolic content of 7.941 mg GAE/g at concentration of 5µg/ml. As for flavonoids content, plant extract showed 21.7 mg RE/g at concentration of 200µg/ml and 43.4 mg RE/g at concentration of 400µg/ml. For antioxidant activity, the plant extract showed weak antioxidant activity in DPPH scavenging activity assay. For antimicrobial test, the leaf extract of C. woodsonii showed weak antimicrobial activity. Conclusion: From this study, it can conclude that C. woodsonii leaf extract possess weak antioxidant activity and weak antimicrobial activity which need to be further validated by using more antioxidant assays and antimicrobial tests.